PENGARUH LINGKUNGAN KERJA NON FISIK (NON-PHYSICAL WORK ENVIRONMENT) DAN DISIPLIN KERJA (WORK DISCIPLINE) TERHADAP KINERJA (JOB PERFORMANCE) DENGAN SEMANGAT KERJA (WORK SPIRIT) SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan Bagian Produksi PT.Maxim Indowood Jepara) - Ellena Vaganza June; Edy Raharja (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT The aim of this study was to analyze the effect of Non-Physical Work Environment, Work Discipline, and Work Spirit on Job Performance. Based on data on the performance of employees in the production department of PT Maxim Indowood Jepara, it shows that the company's targets have not been achieved properly and there has been a decrease in performance in 2020-2022. This phenomenon of decreased performance is what underlies this research. On the other hand, there are still inconsistencies in the results of previous studies regarding the influence of the non-physical work environment and work discipline on employee performance which are proven to have a significant and insignificant effect. This shows that efforts to improve employee performance through non-physical work environment factors and work discipline still cannot guarantee a harmonious relationship. The data used in this study are primary data in the form of questionnaires totaling 105 respondents of PT Maxim Indowood Jepara production employees. The sampling technique used in this research was purposive sampling. The analysis of this research uses Partial Least Square (PLS). Data processing in this study using SmartPLS software version 3.2.8. The results showed that (1) Non-Physical Work Environment has a positive and significant effect on Job Performance. (2) Non-Physical Work Environment has a positive and significant effect on Work Spirit (3) Work Discipline has a negative and insignificant effect on Job Performance (4) Work Discipline has a positive and significant effect on Work Spirit (5) Work spirit has a positive and significant effect on Job Performance.